Molecular identification of nocardia isolates from clinical samples and an overview of human nocardiosis in Brazil. - Paulo Victor Pereira Baio; Juliana Nunes Ramos; Louisy Sanches dos Santos; Morgana Fonseca Soriano; Elisa Martins Ladeira; Mônica Cristina Souza; Thereza Cristina Ferreira Camello; Marcio Garcia Ribeiro; Raphael Hirata Junior; Verônica Viana Vieira; Ana Luíza Mattos-Guaraldi (Public Library of Science (PLoS), 2013)
Background Nocardia sp. causes a variety of clinical presentations. The incidence of nocardiosis varies geographically according to several factors, such as the prevalence of HIV infections, transplants, neoplastic and rheumatic diseases, as well as climate, socio-economic conditions and laboratory procedures for Nocardia detection and identification. In Brazil the paucity of clinical reports of Nocardia infections suggests that this genus may be underestimated as a cause of human diseases and/or either neglected or misidentified in laboratory specimens. Accurate identification of Nocardia species has become increasingly important for clinical and epidemiological investigations. In this study, seven clinical Nocardia isolates were identified by multilocus sequence analysis (MLSA) and their antimicrobial susceptibility was also determined. Most Nocardia isolates were associated to pulmonary disease. Methodology/principal findings The majority of Brazilian human isolates in cases reported in literature were identified as Nocardia sp. Molecular characterization was used for species identification of Nocardia nova, Nocardia cyriacigeorgica, Nocardia asiatica and Nocardia exalbida/gamkensis. Data indicated that molecular analysis provided a different Nocardia speciation than the initial biochemical identification for most Brazilian isolates. All Nocardia isolates showed susceptibility to trimethoprim-sulfamethoxazole, the antimicrobial of choice in the treatment nocardiosis. N. nova isolated from different clinical specimens from one patient showed identical antimicrobial susceptibility patterns and two distinct clones. Conclusions/significance Although Brazil is the world's fifth-largest country in terms of land mass and population, pulmonary, extrapulmonary and systemic forms of nocardiosis were reported in only 6 of the 26 Brazilian states from 1970 to 2013. A least 33.8% of these 46 cases of nocardiosis proved fatal. Interestingly, coinfection by two clones may occur in patients presenting nocardiosis. Nocardia infection may be more common throughout the Brazilian territory and in other developing tropical countries than is currently recognized and MLSA should be used more extensively as an effective method for Nocardia identification.